Front Cover: Two Novel Three‐Dimensional Tetraphenylethylene‐Based Rare Earth MOFs with Ultra‐High Proton Conductivity and Performance Stability (Chem. Eur. J. 60/2022). Issue 60 (17th October 2022) - Wang, Shuyu; Zhao, Lijia; Sun, Hanxu; Wu, Yuanyuan; Wang, Ruidong; Zhang, Suoshu; Du, Lin; Zhao, Qi‐Hua
Abstract : Eu‐ETTB and Gd‐ETTB were obtained by self‐assembly ; their three‐dimensional frameworks provide a channel for proton conduction. Under high humidity, water molecules are adsorbed in the channel and form complex hydrogen bond networks, shown as lightning. Astronauts moving easily along the channel represent the effective transport of protons: proton conductivity reached a maximum value of 2.63×10 −2  S cm −1 . More information can be found in the Research Article by L. Du, Q.‐H. Zhao, and co‐workers (DOI: 10.1002/chem.202202154 ).